2018
DOI: 10.1021/acs.macromol.8b00573
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Thermoplastic Polymers Synthesized by Thiol–Ene Click Chemistry: Examples of Thiol–Norbornene and Thiol–Maleimide Click Reactions

Abstract: Thiol–ene click reactions are used to synthesize segmented thermoplastic materials for the first time via a soft segment + hard segment + chain extender approach that is commonly used to synthesize thermoplastic polyurethane elastomer (TPU). We employ a relatively long chain difunctional thiol (2500 g/mol) as soft segment, a small-molecule thiol as chain extender, and rigid cyclic-ene monomers, including norbornene (containing either urethane or urea linkages in the backbone) and maleimide, as hard segments to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…The vibration peaks at 1684 cm −1 and 1649 cm −1 were attributed to the urethane groups and ester groups, respectively. Compared with Figure 4, the C=O vibration peak at 1691 cm −1 shifted to lower wavenumbers of 1684 cm −1 , which indicated that the epoxy group provided additional hydrogen bonding for HNIPU [42,43]. Further, Scheme 4 showed the additional hydroxyl groups because of the ring opening of epoxy groups, which could lead to more hydrogen bonding.…”
Section: Resultsmentioning
confidence: 95%
“…The vibration peaks at 1684 cm −1 and 1649 cm −1 were attributed to the urethane groups and ester groups, respectively. Compared with Figure 4, the C=O vibration peak at 1691 cm −1 shifted to lower wavenumbers of 1684 cm −1 , which indicated that the epoxy group provided additional hydrogen bonding for HNIPU [42,43]. Further, Scheme 4 showed the additional hydroxyl groups because of the ring opening of epoxy groups, which could lead to more hydrogen bonding.…”
Section: Resultsmentioning
confidence: 95%
“…TEC reactions for polymer synthesis and functionalization are commonly deemed as “click” reactions due to their high chemical- and regio-selectivity, insensitivity to solvent and water, full atom economy, and typically rapid kinetics that afford quantitative conversions. This behavior has led to the use of the TEC reactions and the similar radical-mediated thiol–yne reaction, which possess the same click-like characteristics, ,,, for the synthesis of advanced functional materials, particularly linear step-growth polymers, covalent adaptable networks (CANs), and functionalized surfaces or macromolecules. Further, because TEC reactions do not require toxic metal catalysts and are generally orthogonal to many organic functional groups present in biomolecules, TEC is widely used for bioconjugation strategies as well as for the formation and modification of cell-encapsulating hydrogels. , …”
mentioning
confidence: 99%
“…NPM is intensively used to detect sulfhydryl groups. [ 64–66 ] In the present work, the polythioletheroligomer was prepared at a molar ratio of [BDMT]:[DEGVE] = 1.5:1 and the reaction time was 4 h. Then, the obtained polythiolether was purified and mixed with 0.5 g of NPM with anisole as the solvent. After 12 h of reaction, the product was purified for characterization.…”
Section: Methodsmentioning
confidence: 99%